Two-component addition type heat-conducting gel as well as preparation method and application thereof
By introducing aluminum hydroxide and zinc oxide in thermal conductivity, combined with ethylene silicon oil and other materials, two components are prepared to add a combined heating gel, which solves the problem of lack of low -density and heat conductivity of the existing thermal conductivity. Efficient battery module heat dissipation effect.
Patent Information
- Application Number
- CN202411646106.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing thermal conductivity glue cannot achieve low density and high thermal conductivity in battery modules, and there are problems of insufficient extrusion and settlement resistance.
The dual -component bonus heating gel is adopted, and the modified aluminum hydroxide and modified zinc oxide are introduced in the raw material system. Combined with ethylene silicon oil and other silicon oil to prepare a low -density and high heat conductive thermal gel.
The low density and high thermal conductivity of thermal gels meet the lightweight requirements of new energy vehicles, and at the same time have good extrusion and anti -sinking reduction.
Smart Images

Figure BDA0005139736260000091 
Figure BDA0005139736260000101 
Figure BDA0005139736260000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal conductive gels, and relates to a two-component addition-type thermal conductive gel and a preparation method and application thereof. Background Art
[0002] With the development of new energy vehicles, the motor power of new energy vehicles is getting higher and higher, and with it comes the problem of battery heat dissipation. Therefore, it is necessary to improve the heat dissipation performance of the battery module to match the high power of the motor.
[0003] The existing thermal conductive adhesive can play a role in heat conduction and heat dissipation in battery modules, but the density of the current thermal conductive adhesive is too high. If the thermal conductivity is 2.0W·m -1 ·K -1 , then the density must be 2.5 g·cm -3 The above means that the existing thermal conductive adhesive cannot achieve the characteristics of low density and high thermal conductivity.
[0004] Therefore, it is desirable in the art to provide a thermally conductive gel having low density, high thermal conductivity, good extrudability and anti-settling properties. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a two-component addition-type thermally conductive gel and a preparation method and application thereof.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a two-component addition-type thermally conductive gel, wherein the two-component addition-type thermally conductive gel comprises a component A and a component B;
[0008] The raw materials for preparing the A component include vinyl silicone oil, terminal hydrogen silicone oil, cross-linked hydrogen silicone oil, thermal conductive filler and inhibitor;
[0009] The raw materials for preparing the B component include vinyl silicone oil, thermal conductive filler and catalyst;
[0010] The thermal conductive fillers in the A component and the B component both include modified aluminum hydroxide and modified zinc oxide.
[0011] The two-component addition-type thermally conductive gel provided by the present invention introduces modified aluminum hydroxide and modified zinc oxide into the raw material system, so that the prepared thermally conductive gel has both low density and high thermal conductivity, which can well meet the lightweight requirements of new energy vehicles and has good extrusion and anti-settling properties.
[0012] Preferably, the surfaces of the modified aluminum hydroxide and the modified zinc oxide are grafted with hydroxyethyl methacrylate and 3-methacryloxypropyltrimethoxysilane.
[0013] Preferably, the average particle size of the modified aluminum hydroxide is 6 to 10 μm, for example, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, etc.
[0014] Preferably, the average particle size of the modified zinc oxide is 5 to 10 μm, for example, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, etc.
[0015] Preferably, the modified aluminum hydroxide in component A accounts for 45-60wt% of the total weight of the raw materials for preparing component A, for example 45wt%, 48wt%, 50wt%, 52wt%, 54wt%, 56wt%, 58wt%, 60wt% and the like.
[0016] Preferably, the modified zinc oxide in component A accounts for 25-40wt% of the total weight of the raw materials for preparing component A, for example 25wt%, 28wt%, 30wt%, 32wt%, 34wt%, 36wt%, 38wt%, 40wt%, etc.
[0017] Preferably, the modified aluminum hydroxide in the B component accounts for 45-60wt% of the total weight of the raw materials for preparing the B component, for example 45wt%, 48wt%, 50wt%, 52wt%, 54wt%, 56wt%, 58wt%, 60wt% and the like.
[0018] Preferably, the modified zinc oxide in the B component accounts for 25-40wt% of the total weight of the raw materials for preparing the B component, for example, 25wt%, 28wt%, 30wt%, 32wt%, 34wt%, 36wt%, 38wt%, 40wt%, etc.
[0019] The invention increases the usage ratio of aluminum hydroxide, can achieve high thermal conductivity and relatively low density, and adds zinc oxide to improve the anti-sedimentation property of the system.
[0020] Preferably, the modified aluminum hydroxide or the modified zinc oxide is prepared by the following method:
[0021] (1) using a vinyl silane coupling agent hydrolyzate to perform surface modification on aluminum hydroxide or zinc oxide to obtain a modified intermediate product;
[0022] (2) adding the modified intermediate product to an aqueous emulsifier solution, mixing, then adding hydroxyethyl methacrylate and part of the initiator, and performing a primary polymerization under heating conditions; after the reaction is completed, adding the remaining initiator and 3-methacryloxypropyltrimethoxysilane, performing a secondary polymerization, filtering, washing, and drying to obtain the modified aluminum hydroxide or the modified zinc oxide.
[0023] In the present invention, although the addition of zinc oxide can improve the anti-settling property of the thermal conductive gel, excessive addition of zinc oxide will make the colloid unstable, and the gel will become soft after one or two months. The present invention uses the above method to modify aluminum hydroxide and zinc oxide at the same time on the basis of adding zinc oxide. The synergistic effect of the two can improve the anti-settling property of the thermal conductive gel.
[0024] Preferably, the viscosity of the vinyl silicone oil in component A and component B is each independently 100 to 10000 mPa·s, for example, 100 mPa·s, 300 mPa·s, 500 mPa·s, 800 mPa·s, 1000 mPa·s, 2000 mPa·s, 3000 mPa·s, 5000 mPa·s, 8000 mPa·s, 10000 mPa·s, etc., and the vinyl content is each independently 0.05 to 0.4 mmol / g, for example, 0.05 mmol / g, 0.08 mmol / g, 0.1 mmol / g, 0.2 mmol / g, 0.3 mmol / g, 0.4 mmol / g, etc.
[0025] Preferably, the viscosity of the end-hydrogen silicone oil and the cross-linked hydrogen silicone oil is independently 5 to 500 mPa·s, for example, 5 mPa·s, 10 mPa·s, 30 mPa·s, 50 mPa·s, 80 mPa·s, 100 mPa·s, 200 mPa·s, 300 mPa·s, 400 mPa·s, 500 mPa·s, etc.
[0026] Preferably, the content of silicon hydrogen groups in the terminal hydrogen-containing silicone oil is 0.15 to 2 mmol / g, for example, 0.15 mmol / g, 0.3 mmol / g, 0.5 mmol / g, 0.8 mmol / g, 1 mmol / g, 1.3 mmol / g, 1.5 mmol / g, 1.8 mmol / g, 2 mmol / g, etc.
[0027] Preferably, the content of silicon hydrogen groups in the cross-linked hydrogen silicone oil is 1 to 10 mmol / g, for example, 1 mmol / g, 2 mmol / g, 3 mmol / g, 5 mmol / g, 8 mmol / g, 10 mmol / g, etc.
[0028] Preferably, the molar ratio of the silyl groups in the hydrogen-terminated silicone oil to the vinyl groups in the preparation raw material system is 0.6 to 0.9, such as 0.6, 0.7, 0.8, 0.9, etc.
[0029] Preferably, the molar ratio of the silicon hydrogen group in the cross-linked hydrogen silicone oil to the vinyl group in the preparation raw material system is 0.05 to 0.3, for example, 0.05, 0.08, 0.1, 0.2, 0.3, etc.
[0030] Preferably, the molar ratio of silyl groups to vinyl groups in the preparation raw material system is 0.65 to 0.95, for example, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, etc.
[0031] Preferably, the inhibitor includes any one of 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, 1,1,3,3-tetramethyl-1,3-divinylsiloxane, 3-methyl-1-butyn-3-ol, 1-ethynylcyclohexanol, 3-phenyl-1-butyn-3-ol, 3-propyl-1-butyn-3-ol, and 3-octyl-1-butyn-3-ol, or a combination of at least two thereof.
[0032] Preferably, the catalyst comprises a platinum catalyst (organic platinum complex).
[0033] Preferably, the catalyst comprises any one of an alcohol solution of chloroplatinic acid, a platinum catalyst coordinated with tetrahydrofuran, and a platinum catalyst coordinated with divinyltetramethylsiloxane, or a combination of at least two thereof.
[0034] Preferably, the amount of the catalyst added is 1 to 10 ppm of the total weight of all the raw materials for preparing components A and B, such as 1 ppm, 3 ppm, 5 ppm, 8 ppm, 10 ppm, etc.
[0035] Preferably, the raw materials for preparing component B also include color paste, and the added amount is preferably 0.01-0.5% (based on the total weight of all the raw materials for preparing components A and B).
[0036] Preferably, the weight ratio of component A to component B is (0.8-1.2):1, wherein 0.8-1.2 can be, for example, 0.8, 0.9, 1, 1.1, 1.2, etc.
[0037] The present invention selects a suitable oil-powder ratio and selects suitable powder and oil (wherein the powder refers to the thermal conductive filler and the oil refers to the remaining other components) so that the thermal conductive gel has a suitable viscosity, is convenient for extrusion construction, and has a lower density and a higher thermal conductivity.
[0038] In addition, the thermally conductive gel provided by the present invention is not prone to oil precipitation, and its thermal conductivity is stable for a long time after curing; by controlling the molar ratio of the cross-linked hydrogen silicone oil, the terminal hydrogen silicone oil and the silicon hydrogen group to the vinyl group of the thermally conductive gel as a whole, a thermally conductive gel with moderate adhesion to the substrate and appropriate hardness and softness can be obtained, which can facilitate peeling and rework while ensuring the buffering and shock-absorbing effect of the thermally conductive gel.
[0039] In a second aspect, the present invention provides a method for preparing the two-component addition-type thermally conductive gel as described in the first aspect, the preparation method comprising the following steps:
[0040] (1) mixing vinyl silicone oil, terminal hydrogen silicone oil, cross-linked hydrogen silicone oil, thermal conductive filler and inhibitor to obtain the A component;
[0041] (2) mixing vinyl silicone oil, thermal conductive filler and catalyst to obtain the B component;
[0042] (3) Mixing component A and component B to obtain the two-component addition-type thermal conductive gel.
[0043] In a third aspect, the present invention provides an application of the two-component addition-type thermally conductive gel as described in the first aspect in a new energy battery assembly.
[0044] Compared with the prior art, the present invention has at least the following beneficial effects:
[0045] The two-component addition-type thermally conductive gel provided by the present invention introduces modified aluminum hydroxide and modified zinc oxide into the raw material system, so that the prepared thermally conductive gel has a low density (1.887-1.987 g·cm -3 ) and high thermal conductivity (2.096~2.185W·m -1 ·K -1 ), which can well meet the lightweight requirements of new energy vehicles, and at the same time has good extrusion properties (5.68 ~ 6.14g) and anti-settling properties. DETAILED DESCRIPTION
[0046] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0047] Unless otherwise specified, some of the raw material information used in the following preparation examples of the present invention is as follows:
[0048] Fatty alcohol polyoxyethylene ether: brand number is 68439509.
[0049] Preparation Example 1-A
[0050] In this preparation example, a modified aluminum hydroxide is provided, which is prepared according to the following method:
[0051] (1) Add 10 g of vinyltrimethoxysilane to 5 L of aqueous solution at pH 3, stir for 10 min, then add 1 kg of aluminum hydroxide to perform surface modification, filter and wash with water until neutral, to obtain a modified intermediate product;
[0052] (2) Add 200g of fatty alcohol polyoxyethylene ether to 10L of water, stir and mix until the solution is clear, add 1kg of the modified intermediate product prepared above, and stir for 30min; then, under stirring, drop 4kg of hydroxyethyl methacrylate and 0.4kg of ammonium persulfate aqueous solution (10wt%), react at 80°C, and complete the primary polymerization after 6h. Then, continue to add 1.5kg of 3-methacryloxypropyltrimethoxysilane and 0.2kg of ammonium persulfate aqueous solution (10wt%) under stirring at 80°C, and carry out secondary polymerization. After 5h, the reaction is completed, filtered, washed, and dried to obtain the modified aluminum hydroxide.
[0053] Preparation Example 1-B
[0054] In this preparation example, a modified zinc oxide is provided, which is different from Preparation Example 1-A only in that the aluminum hydroxide in step (1) is replaced by an equal amount of zinc oxide.
[0055] Preparation Example 2-A
[0056] In this preparation example, a modified aluminum hydroxide is provided, which is prepared according to the following method:
[0057] (1) Add 15 g of vinyltriethoxysilane to 5 L of aqueous solution at pH 5, stir for 10 min, then add 1 kg of aluminum hydroxide to perform surface modification, filter and wash with water until neutral, to obtain a modified intermediate product;
[0058] (2) 300g of fatty alcohol polyoxyethylene ether was added to 10L of water, stirred and mixed until the solution was clear, 1kg of the modified intermediate product prepared above was added, and stirred for 20min; then 3kg of hydroxyethyl methacrylate and 0.5kg of ammonium persulfate aqueous solution (10wt%) were added dropwise under stirring conditions, and the reaction was carried out at a constant temperature of 85°C, and the primary polymerization was completed after 5h. Then, 2kg of 3-methacryloxypropyltrimethoxysilane and 0.2kg of ammonium persulfate aqueous solution (10wt%) were added dropwise under stirring at a temperature of 85°C to carry out secondary polymerization, and the reaction was completed after 5h, and the modified aluminum hydroxide was obtained by filtering, washing, and drying.
[0059] Preparation Example 2-B
[0060] In this preparation example, a modified zinc oxide is provided, which differs from Preparation Example 2-A only in that the aluminum hydroxide in step (1) is replaced by an equal amount of zinc oxide.
[0061] Preparation Example 3-A
[0062] In this preparation example, a modified aluminum hydroxide is provided, which is prepared according to the following method:
[0063] (1) Add 15 g of vinyltriethoxysilane to 5 L of aqueous solution at pH 4, stir for 10 min, then add 1 kg of aluminum hydroxide to perform surface modification, filter and wash with water until neutral, to obtain a modified intermediate product;
[0064] (2) Add 250g of fatty alcohol polyoxyethylene ether to 10L of water, stir and mix until the solution is clear, add 1kg of the modified intermediate product prepared above, and stir for 30min; then, under stirring, add 5kg of hydroxyethyl methacrylate and 0.75kg of ammonium persulfate aqueous solution (10wt%), and react at a constant temperature of 80°C to complete the primary polymerization after 6h. Then, continue to add 1kg of 3-methacryloxypropyltrimethoxysilane and 0.2kg of ammonium persulfate aqueous solution (10wt%) under stirring at 80°C to carry out secondary polymerization. After 6h, the reaction is completed, filtered, washed, and dried to obtain the modified aluminum hydroxide.
[0065] Preparation Example 3-B
[0066] In this preparation example, a modified zinc oxide is provided, which differs from Preparation Example 3-A only in that the aluminum hydroxide in step (1) is replaced by an equal amount of zinc oxide.
[0067] Preparation Example 4-A
[0068] In this preparation example, a modified aluminum hydroxide is provided, which differs from Preparation Example 1-A only in that, in step (2), an equal amount of 3-methacryloxypropyltrimethoxysilane is used to replace hydroxyethyl methacrylate.
[0069] Preparation Example 4-B
[0070] In this preparation example, a modified zinc oxide is provided, which differs from Preparation Example 4-A only in that the aluminum hydroxide in step (1) is replaced by an equal amount of zinc oxide.
[0071] Preparation Example 5-A
[0072] In this preparation example, a modified aluminum hydroxide is provided, which differs from Preparation Example 1-A only in that, in step (2), an equal amount of hydroxyethyl methacrylate is used to replace 3-methacryloxypropyltrimethoxysilane.
[0073] Preparation Example 5-B
[0074] In this preparation example, a modified zinc oxide is provided, which differs from Preparation Example 5-A only in that the aluminum hydroxide in step (1) is replaced by an equal amount of zinc oxide.
[0075] Preparation Example 6-A
[0076] In this preparation example, a modified aluminum hydroxide is provided, which differs from Preparation Example 1-A only in that, in step (2), an equal amount of methyl methacrylate is used instead of hydroxyethyl methacrylate.
[0077] Preparation Example 6-B
[0078] In this preparation example, a modified zinc oxide is provided, which differs from Preparation Example 6-A only in that the aluminum hydroxide in step (1) is replaced by an equal amount of zinc oxide.
[0079] Preparation Example 7-A
[0080] In this preparation example, a modified aluminum hydroxide is provided, which differs from Preparation Example 1-A only in that, in step (2), an equal amount of glycidyl methacrylate is used to replace 3-methacryloxypropyltrimethoxysilane.
[0081] Preparation Example 7-B
[0082] In this preparation example, a modified zinc oxide is provided, which differs from Preparation Example 7-A only in that the aluminum hydroxide in step (1) is replaced by an equal amount of zinc oxide.
[0083] Example 1
[0084] In this embodiment, a two-component addition-type thermally conductive gel is provided. The two-component addition-type thermally conductive gel comprises a component A and a component B. The preparation method comprises the following steps:
[0085] (1) 12 g of a vinyl silicone oil having a viscosity of 1000 cs and a vinyl content of 0.12 mmol / g, 20 g of a vinyl silicone oil having a viscosity of 200 cs and a vinyl content of 0.27 mmol / g, 15 g of a terminal hydrogenated silicone oil having a viscosity of 40 cs and a hydrogen content of 0.8 mmol / g, 0.95 g of a cross-linked hydrogenated silicone oil having a viscosity of 30 cs and a hydrogen content of 2.0 mmol / g, 210 g of a modified aluminum hydroxide having a particle size of 6 μm (prepared in Preparation Example 1-A), 150 g of a modified zinc oxide having a particle size of 5 μm (prepared in Preparation Example 1-B) and 0.05 g of an inhibitor (2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane) were mixed uniformly to obtain component A;
[0086] (2) 47.6 g of vinyl silicone oil with a viscosity of 200 cs and a vinyl content of 0.27 mmol / g, 210 g of modified aluminum hydroxide with a particle size of 6 μm (prepared by Preparation Example 1-A), 150 g of modified zinc oxide with a particle size of 5 μm (prepared by Preparation Example 1-B) and 0.4 g of platinum catalyst (alcohol solution of chloroplatinic acid, platinum content of 1 wt%) were mixed uniformly to obtain component B;
[0087] (3) Component A and component B are mixed evenly in a mass ratio of 1:1 to obtain the two-component addition-type thermal conductive gel.
[0088] Example 2-Example 6
[0089] The difference between Example 2 to Example 6 and Example 1 is that the selection and dosage of specific raw materials are different, as shown in Table 1. The contents not shown in Table 1 are the same as those in Example 1.
[0090] Table 1
[0091]
[0092]
[0093] Example 7
[0094] The only difference between this embodiment and embodiment 1 is that the modified aluminum hydroxide in step (1) and step (2) is replaced by a corresponding equal amount of modified aluminum hydroxide provided in Preparation Example 4-A, and the modified zinc oxide in step (1) and step (2) is replaced by a corresponding equal amount of modified zinc oxide provided in Preparation Example 4-B.
[0095] Example 8
[0096] The only difference between this embodiment and embodiment 1 is that the modified aluminum hydroxide in step (1) and step (2) is replaced by a corresponding equal amount of modified aluminum hydroxide provided in Preparation Example 5-A, and the modified zinc oxide in step (1) and step (2) is replaced by a corresponding equal amount of modified zinc oxide provided in Preparation Example 5-B.
[0097] Example 9
[0098] The only difference between this embodiment and embodiment 1 is that the modified aluminum hydroxide in step (1) and step (2) is replaced by a corresponding equal amount of modified aluminum hydroxide provided in Preparation Example 6-A, and the modified zinc oxide in step (1) and step (2) is replaced by a corresponding equal amount of modified zinc oxide provided in Preparation Example 6-B.
[0099] Example 10
[0100] The only difference between this embodiment and embodiment 1 is that the modified aluminum hydroxide in step (1) and step (2) is replaced by a corresponding equal amount of modified aluminum hydroxide provided in Preparation Example 7-A, and the modified zinc oxide in step (1) and step (2) is replaced by a corresponding equal amount of modified zinc oxide provided in Preparation Example 7-B.
[0101] Comparative Example 1
[0102] The only difference between this comparative example and Example 1 is that the modified aluminum hydroxide in step (1) and step (2) is replaced by unmodified aluminum hydroxide (D50 particle size 6 μm).
[0103] Comparative Example 2
[0104] The only difference between this comparative example and Example 1 is that the modified zinc oxide in step (1) and step (2) is replaced by unmodified zinc oxide (D50 particle size 5 μm).
[0105] The performance of the two-component addition-type thermally conductive gel provided in the embodiment and the comparative example was tested, and the testing method was as follows:
[0106] (1) Tensile strength and elongation at break test: measured in accordance with the provisions of GB / T 528;
[0107] (2) Shore 00 hardness test: measured in accordance with the provisions of GB / T 531;
[0108] (3) Peel force test: measured in accordance with the provisions of GB / T 7124;
[0109] (4) Thermal conductivity test: measured in accordance with the provisions of ISO 22007-2;
[0110] (5) Density test: Determine in accordance with the provisions of GB / T 533;
[0111] (6) Extrusion test: Use a 30cc syringe, a 14# (1.54mm inner diameter) needle, and a pressure of 90psi to test the weight of the glue that flows out within 1 minute;
[0112] (7) Anti-sedimentation (anti-oiling) performance test: Take 200g of component A and 200g of component B respectively and put them into disposable plastic cups. After leaving them at room temperature (23±2℃) for one month, observe whether there is liquid oil precipitation on the surface. If there is no silicone oil precipitation on the surface, it means that its anti-sedimentation (oiling) performance is good; if there is silicone oil precipitation on the surface but it cannot flow, the anti-oiling performance is considered to be average; if there is silicone oil precipitation on the surface and the silicone oil is relatively large and can flow, the anti-oiling performance is considered to be poor.
[0113] The performance test results are shown in Table 2.
[0114] Table 2
[0115]
[0116] It can be seen from Table 2 that the two-component addition-type thermally conductive gel provided in Examples 1-6 of the present invention has a low density (1.887-1.987 g·cm -3 ) and high thermal conductivity (2.096~2.185W·m -1 ·K -1 ), and has good extrudability (5.68-6.14 g) and anti-settling properties.
[0117] Compared with Example 1, the mechanical properties, extrudability and anti-settling properties of the two-component addition-type thermally conductive gel provided in Comparative Examples 1-2 are significantly deteriorated.
[0118] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the two-component addition-type thermally conductive gel and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A two-component addition-type thermally conductive gel, characterized in that: The two-component addition-type thermally conductive gel comprises component A and component B; The raw materials for preparing the A component include vinyl silicone oil, terminal hydrogen silicone oil, cross-linked hydrogen silicone oil, thermal conductive filler and inhibitor; The raw materials for preparing the B component include vinyl silicone oil, thermal conductive filler and catalyst; The thermal conductive fillers in the A component and the B component both include modified aluminum hydroxide and modified zinc oxide.
2. The two-component addition-type thermally conductive gel according to claim 1, characterized in that: The surfaces of the modified aluminum hydroxide and the modified zinc oxide are grafted with hydroxyethyl methacrylate and 3-methacryloxypropyltrimethoxysilane; Preferably, the average particle size of the modified aluminum hydroxide is 6 to 10 μm; Preferably, the average particle size of the modified zinc oxide is 5 to 10 μm.
3. The two-component addition-type thermally conductive gel according to claim 1 or 2, characterized in that: The modified aluminum hydroxide in the A component accounts for 45-60wt% of the total weight of the raw materials for preparing the A component; Preferably, the modified zinc oxide in the A component accounts for 25-40 wt% of the total weight of the raw materials for preparing the A component; Preferably, the modified aluminum hydroxide in the B component accounts for 45-60wt% of the total weight of the raw materials for preparing the B component; Preferably, the modified zinc oxide in the B component accounts for 25-40 wt % of the total weight of the raw materials for preparing the B component.
4. The two-component addition-type thermally conductive gel according to any one of claims 1 to 3, characterized in that: The modified aluminum hydroxide or the modified zinc oxide is prepared by the following method: (1) using a vinyl silane coupling agent hydrolyzate to perform surface modification on aluminum hydroxide or zinc oxide to obtain a modified intermediate product; (2) adding the modified intermediate product to an aqueous emulsifier solution, mixing, then adding hydroxyethyl methacrylate and part of the initiator, and performing a primary polymerization under heating conditions; after the reaction is completed, adding the remaining initiator and 3-methacryloxypropyltrimethoxysilane, performing a secondary polymerization, filtering, washing, and drying to obtain the modified aluminum hydroxide or the modified zinc oxide.
5. The two-component addition-type thermally conductive gel according to any one of claims 1 to 4, characterized in that: The viscosity of the vinyl silicone oil in the A component and the B component is independently 100 to 10000 mPa·s, and the vinyl content is independently 0.05 to 0.4 mmol / g.
6. The two-component addition-type thermally conductive gel according to any one of claims 1 to 5, characterized in that: The viscosity of the terminal hydrogen silicone oil and the cross-linked hydrogen silicone oil is independently 5 to 500 mPa·s; Preferably, the content of silicon hydrogen groups in the hydrogen-terminated silicone oil is 0.15 to 2 mmol / g; Preferably, the content of silicon hydrogen groups in the cross-linked hydrogen silicone oil is 1 to 10 mmol / g; Preferably, the molar ratio of the silicon hydrogen group in the terminal hydrogen-containing silicone oil to the vinyl group in the preparation raw material system is 0.6 to 0.9; Preferably, the molar ratio of the silicon hydrogen group in the cross-linked hydrogen silicone oil to the vinyl group in the preparation raw material system is 0.05 to 0.3; Preferably, the molar ratio of silyl groups to vinyl groups in the raw material system is 0.65 to 0.
95.
7. The two-component addition-type thermally conductive gel according to any one of claims 1 to 6, characterized in that: The inhibitor includes any one of 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, 1,1,3,3-tetramethyl-1,3-divinylsiloxane, 3-methyl-1-butyn-3-ol, 1-ethynylcyclohexanol, 3-phenyl-1-butyn-3-ol, 3-propyl-1-butyn-3-ol, and 3-octyl-1-butyn-3-ol, or a combination of at least two thereof; Preferably, the catalyst comprises a platinum catalyst; Preferably, the catalyst comprises any one or a combination of at least two of an alcohol solution of chloroplatinic acid, a platinum catalyst coordinated with tetrahydrofuran, and a platinum catalyst coordinated with divinyltetramethylsiloxane; Preferably, the catalyst is added in an amount of 1 to 10 ppm based on the total weight of all the raw materials for preparing the A component and the B component.
8. The two-component addition-type thermally conductive gel according to any one of claims 1 to 7, characterized in that: The weight ratio of component A to component B is (0.8-1.2):
1.
9. A method for preparing a two-component addition-type thermally conductive gel according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: (1) mixing vinyl silicone oil, terminal hydrogen silicone oil, cross-linked hydrogen silicone oil, thermal conductive filler and inhibitor to obtain the A component; (2) mixing vinyl silicone oil, thermal conductive filler and catalyst to obtain the B component; (3) Mixing component A and component B to obtain the two-component addition-type thermal conductive gel.
10. Use of the two-component addition-type thermally conductive gel according to any one of claims 1 to 8 in a new energy battery assembly.
Citation Information
Patent Citations
Bi-component heat conduction silica gel and application thereof
CN104513487A
Addition type heat-conducting pouring sealant and preparation method thereof
CN115340844A
Surface-modified zinc oxide particles, dispersion liquid, and cosmetic
CN115485242A
Bi-component addition type heat-conducting glue and preparation method thereof
CN115491170A
Two-component heat-conducting gel as well as preparation method and application thereof
CN116285366A
Cited By
Heat-conducting gel as well as application and use method thereof
CN122037585A